Low Fidelity Contained Manual Tissue Extraction Simulation Improves Resident Confidence [3H]. (May 2016) - Saad, Christina A.; Templeman, Claire; Jaque, Jenny M.; Minneti, Michael
Abstract : INTRODUCTION: Controversy surrounding power morcellators triggered an FDA warning resulting in multiple hospitals banning the device. Physicians have had to revert to alternate tissue extraction techniques for large specimens. We developed a simulation to allow physicians to practice contained manual tissue extraction. METHODS: We created a low fidelity simulator and filmed an instructional video depicting contained tissue extraction techniques. 4th year residents answered a questionnaire assessing their baseline exposure and confidence level with contained tissue extraction, then they each extracted a 355 g beef tongue specimen from our simulator while being timed. They then viewed the instructional video then once again extracted another 355 g beef tongue specimen. Following the simulation, they answered another survey question regarding their confidence level. RESULTS: Six 4th year residents participated. Four had ever seen power morcellation, one had ever performed it, none had seen it in a contained fashion. Six had seen and performed manual morcellation vaginally, but never in a contained fashion. Two had seen and performed manual morcellation abdominally, only one performed it in a contained fashion. The mean confidence level with contained manual tissue extraction of a large specimen increased from 1.83 to 4.17 (SD 0.41, P =.001) with the intervention on a 5-point Likert scale. There was no statistically significant difference in tissue extraction timing. CONCLUSION: Our residents are rarely exposed to morcellation techniques, particularly in a contained fashion. Among 4th year residents, this low fidelity simulation statistically significantly improved their confidence level in regard to contained manual tissue extraction of a large specimen.